An Approach to the Synthesis of Tetrahydroisoquinoline Alkaloids by Alkene Hydroamination: Synthesis of Coralydine - Pouilhès, Annie; Baltaze, Jean-Pierre; Kouklovsky, Cyrille (Synlett, 2013)
The protoberberine alkaloid coralydine was synthesized in a short sequence by a strategy including an intramolecular alkene hydroamination as the key step, followed by a Pictet–Spengler cyclization.
Keywords: alkaloids; total synthesis; nitrogen; heterocycles